Goiás e a guerra do Paraguai (1865 – 1870) - Batista, Igor Euzébio (Universidade Federal do Tocantins, 2022)
This work deals with the participation of Goiás in the Paraguayan War. The objective is to identify important aspects of how the province of Goiás could help the Brazilian empire with war logistics and with the supply of battalions of soldiers and Volunteers of the Motherland. We used as a source of research the reports of the President of the Province and newspapers published between 1865 and 1870, in the province of Goiás. The methodology used starts from the bibliographical reading on the subject, especially that which deals with the province of Goiás. As a result, the research demonstrates having the most central province in the country precariously assisted the Brazilian army that needed to cross the territory of Goiás to fight Paraguay.